Sustainable development of agricultural cooperative among the beneficiaries of Bank of agriculture (boa) loan scheme in Ogun State, Nigeria (West African Journal on Sustainable Development, 2024)
This study focused on sustainable development of Agricultural Cooperative among beneficiaries of Bank of Agriculture (BOA) loan scheme in Ogun state, Nigeria. The three zones of the operation were sampled using multistage sampling techniques. Primary and secondary data were utilized for the study and obtained with the use of a well-structured questionnaire from 120 respondents out of which One hundred and nine (109) were returned, and acceptable for data analysis. The results obtained on the socio-economic characteristics of the (BOA) agricultural cooperators revealed that majority of them were male (58.7%), aged less than 50 years (75.2) with an average age of 42.51 years per cooperators, married (75.2%), had moderate household size of 5 (mean) per household, literate with vast majority (98.2%)  possessing one form of formal education or other, (71.6%), engaged in farming as main occupation had an average of 5 years of farming experience and (64.2%) practiced Christianity as religion. Analysis of the factors influencing the amount of loan obtained revealed that age, education, farm size, amount repaid, loan experience among others. While household size had negative relationship with loan repayment, education and loan size have positive relationship with it. In terms of constraints to the BOA loan acquisition, high interest rate, bureaucracy and inability to provide a guarantor were adjudged as the major constraints.
Keywords: Agricultural Cooperatives; Loan Acquisition; Sustainability; Access to Loan